Agricultural products live streaming E-commerce ecosystem dynamics research - Zhao, Guoyu (Frontiers in Sustainable Food Systems, 2025)
PurposeThis study aims to explore the conceptual framework of the agricultural products live streaming e-commerce ecosystem and construct a theoretical model of the agricultural product live streaming e-commerce ecosystem based on system dynamics. The research findings provide recommendations for the sustainable development of the agricultural product live streaming e-commerce industry.Design/methodology/approachThis study proposes a conceptual model of the agricultural products live streaming e-commerce ecosystem, analyzes the predation, mutual-benefit, competition, and parasitism relationships among the subjects, such as live streaming platforms, agricultural live streamers, and multi-channel network (MCN) agencies in the system, and uses system dynamics methods to establish causal circuit diagrams and simulation models. Reveal the development trends of key industrial indicators and the extent to which ecological relationships affect the system from 2016 to 2046.FindingsThe simulation results indicate: (1) During the period from 2016 to 2046, all key indicators in the agricultural products live streaming e-commerce ecosystem have shown an upward trend; (2) Competition and parasitism relationships have the most significant impact on the system, while predation and mutual-benefit relationships have a relatively weak influence. In practice, priority should be given to supporting live streaming e-commerce platforms and multi-channel network (MCN) agencies to promote the sustainable development of the industry.Originality/valueThis study employs the system dynamics method and, through qualitative and quantitative analysis, reveals the development laws of the live streaming e-commerce industry for agricultural products, and puts forward practical suggestions, providing a new perspective for research in the field of dynamic development.